The Hindu Religion Values Illustrated in Bhagavad Gita For Students and Beginners of Ramananda Prasad - Kusuma Wardani, Ni Ketut; Ariasa Giri, I Made (Jayapangus Press, 2024)
The perception that Hindu religious education is challenging to comprehend due to its complex philosophical language is becoming obsolete in today’s modern context. This study explores the educational values embedded within 26 illustrated stories in the Bhagavad Gita (For Students and Beginners) by Ramananda Prasad. Although universal in nature, these stories often obscure the explicit Hindu religious educational values they convey. As a foundational aspect of personal development, understanding Hindu educational values aids in building self-competence for students and beginners. This study aims to identify and analyze the concept of Hindu religious education values and their presence in the illustrated stories of the Bhagavad Gita by Ramananda Prasad. Utilizing a descriptive qualitative reference method, this research delves into the textual content of the Bhagavad Gita, interpreting its values and their application. The findings reveal that Hindu religious education is a comprehensive framework for imparting knowledge, attitudes, personality, and practical skills aligned with Hindu teachings, specifically related to the Tri Jnana Sandhi (three fundamental aspects of knowledge: Jnana, Vijnana, and Ajna). Three primary educational values emerge from the analysis: religious values, emphasizing devotion and spiritual practice; moral values, focusing on ethical behavior and integrity; and compassion values, highlighting empathy and care for others. In conclusion, the illustrated stories in Ramananda Prasad’s Bhagavad Gita serve as an accessible medium for conveying Hindu educational values, transforming complex teachings into relatable narratives that resonate with both students and beginners in their spiritual and personal growth.